Rancang Bangun Aplikasi Penjualan dan Stok Barang Material (Studi Kasus: Toko Bangunan XYZ) - Triana Elizabeth; Tinaliah Tinaliah (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2018)
The increasing competition in the building materials business in Palembang city makes some businessmen in the field of building materials sales difficult to survive and some others have experienced a decline in sales.Accordingly, business people must be smart to know what items to buy to prevent the accumulation of stock of goods that do not sell so that losses. XYZ Building Store is one store that wants to keep its business. then, it takes a sales and inventory application that can provide information on the quantity stock of goods available, and what is the bestsellers. The method used in the design of this application using iterative method. Making database using DBMS SQL Server and visual basic as programming language. Testing the application using black box testing to determine the function and performance for each menu of the application. The result, this application has met or has been in accordance with the needs. In addition, this application can also improve the performance and efficiency of time in sales transactions and know the stock of current goods that help owners of XYZ building stores to make decisions what items to buy